2004
DOI: 10.1088/0967-3334/25/5/016
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical impedance vector analysis in haemodialysis patients: relation between oedema and mortality

Abstract: In this work, bioelectrical impedance vector analysis (BIVA) method is used in a sample of haemodialysis patients in stable (without oedema) and critical (hyperhydrated and malnutrition) states, in order to establish the relation between hyperhydration (oedema) and mortality. The measurements obtained were single frequency (50 kHz), tetrapolar (hand-foot) complex impedance measurements (vector components are: resistance R and reactance Xc). The impedance components were standardized by the height H of the subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 15 publications
(8 reference statements)
0
38
0
5
Order By: Relevance
“…This type of graph allows us to identify the individual vector migration from the start to the end of the program, using reference population ellipses. In order to explain how we interpret the location of the vector, we are showing in Figure 1 the classification proposed to BIVA analysis [13][14][15]. Vector analysis was performed with BIVA software (Department of Medical and Surgical Sciences, University of Padova, Padova, Italy, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of graph allows us to identify the individual vector migration from the start to the end of the program, using reference population ellipses. In order to explain how we interpret the location of the vector, we are showing in Figure 1 the classification proposed to BIVA analysis [13][14][15]. Vector analysis was performed with BIVA software (Department of Medical and Surgical Sciences, University of Padova, Padova, Italy, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In this technique, the body resistance (R) and reactance (Xc), obtained at 50 kHz, are plotted as a bivariate vector. One of the positive aspects of this kind of analysis, in addition to its low cost, is that it provides values that are independent of regression equations and body weight [13][14][15]. To our knowledge, there is not, currently, any published data describing the use of BIVA analysis in programs of physical activity in healthy obese subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The position and length of the vector provides information about hydration status, body cell mass and cell integrity (Norman et al 2012). This method has been shown to be effective to identify patients with a critical fluid overload (Nescolarde et al 2004). Toso et al (2000) using both the BIA and BIVA methods detected that reactance components decrease in pulmonary disease patients.…”
Section: Introductionmentioning
confidence: 99%
“…This method has been shown to be effective to assess hydration status [8] and identify patients with a critical fluid overload [9]. Walter-Kroker et al [10] using both the BIA and BIVA methods revealed altered nutritional and fluid status in chronic obstructive pulmonary disease patients (e.g.…”
Section: Introductionmentioning
confidence: 99%